Is Breast Conserving Surgery A Suitable Approach for Early Breast Carcinoma? A Multicenter Study - Awni Ismail Sultan, Mohammed Mohammud Habash (Pakistan Journal of Medical & Health Sciences, 2022)
Currently, there has been a tendency to prefer breast-conserving surgery (BCS) over mastectomy (MC). Therefore, this study came to assess whether this is true when compared with mastectomy. This retrospective study included early breast cancer patients who were registered in government and private hospitals in Kirkuk and Diyala governorates during the period from February 2015 to March 2017, and were followed up after surgery for five years. The enrolled patients (women) were set into (2) groups; the first one was for patients treated with BCS, while the second was for patients who underwent MC. As a preliminary result, it was found that out of the total of (172) participants, (72) were in the BCS, and (100) in the MC. Convergence of age groups was observed between patients in both surgical groups. The results proved that the local recurrence rate amounted to about (9%) in patients undergoing BCS and the survival rate was for the same group (97%). Thus, we concluded that the breast preservation approach is an appropriate and successful choice for early breast carcinoma patients. Keywords: carcinoma, conserving surgery, local recurrence.